Impact of online WOM on destination trust and intention to travel: A medical tourism perspective - Abubakar, Mohammed Abubakar; İlkan, Mustafa (Elsevier, 2016)
Electronic word-of-mouth (WOM), also known as eWOM, is one of the most influential sources of information on the web. The aim of this study is to examine the impact of online WOM on destination trust and intention to travel in the medical tourism sector. In addition, the paper examines the moderating effect of income on the researched variables. Structural equation modeling is applied to examine the interplay between the proposed variables, using a sample of 216 respondents. The empirical results suggest that: online WOM positively influences destination trust and intention to travel; destination trust positively influences intention to travel; rising income strengthens the relationship between online WOM and intention to travel; and rising income weakens the relationship between destination trust and intention to travel. Implications and future research directions are discussed.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Online WOM; eWOM; Medical tourism; Destination trust; Travel intention